Morfologi Hemipenis Biawak Air (Varanus salvator bivittatus) - Mahfud Mahfud; Adi Winarto; Chairun Nisa (Jurnal Sain Veteriner, 2017)
Varanus salvator bivittatus has a pair of hemipenes, which is macroscopic anatomically like the copulatory organ in other amniotes, cylindrical-shaped (truncus) with quite flexible, and it located on the base of the caudal tailof the cloaca. However, information about the microscopic anatomy of hemipenes of this animal is scientifically unpublicized. Therefore, the aim of this research is to study the microscopic anatomy of hemipenes of male Varanussalvator bivittatus. The animals were sacrificed by exsanguination under deep anesthetized and fixed in 4 % paraformaldehyde through perfusion then observed visceral site and morphometric. Histomorphological evaluationwas obtained by paraffin preparation with section thickness of 3-4 μm then stained in Hematoxylin-Eosin (HE) and Masson’s Trichrome (MT). The results showed that truncus of hemipenes was lined by stratified squamousepithelium and supported with thick of dense connective tissue and contain cavernous body and blood vessels are found, the muscles not found. The presence of connective tissue that supported in the down part sometimesmake hemipenes are rigid while prurient condition. In the caudal of truncus hemipenes there is retractor muscle of hemipenes which arranged by striated muscles. Hemipenes is flexible because contain with much of blood vesselthat found in truncus hemipenes.